2019
DOI: 10.1002/jbt.22423
|View full text |Cite
|
Sign up to set email alerts
|

Expression signature of miRNAs and the potential role of miR‐195‐5p in high‐glucose–treated rat cardiomyocytes

Abstract: MicroRNAs are endogenous small noncoding RNAs that posttranscriptionally regulate the expression of target genes and play crucial roles in diverse physiopathologic processes. In the current study, we examined the microRNA (miRNA) expression profile of high-glucose-treated neonatal rat cardiomyocytes and the potential mechanisms. Differentially expressed miRNAs were analyzed by a miRNA microarray and validated by a quantitative real-time polymerase chain reaction in high-glucose-treated rat cardiomyocytes. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…For example, research [16] reported that it could inhibit cervical cancer cells' migration and invasion by inhibiting ARL2. Recent studies [17] have found that it plays a crucially regulatory part in myocardial injury induced by high glucose, but its mechanism of action on cardiomyocytes has not been elaborated in detail. In our study, first, we established HF rat model by ligating abdominal aorta, and then we found that it expressed low in myocardium of HF rats.…”
Section: Discussionmentioning
confidence: 99%
“…For example, research [16] reported that it could inhibit cervical cancer cells' migration and invasion by inhibiting ARL2. Recent studies [17] have found that it plays a crucially regulatory part in myocardial injury induced by high glucose, but its mechanism of action on cardiomyocytes has not been elaborated in detail. In our study, first, we established HF rat model by ligating abdominal aorta, and then we found that it expressed low in myocardium of HF rats.…”
Section: Discussionmentioning
confidence: 99%
“…GDM, gestational diabetes mellitus; GH, gestational hypertension; miR, microRNA; PE, preeclampsia; PPCM, peripartum cardiomyopathy male STZ mice, while myocardial capillary density and coronary blood flow were improved [147]. Similarly, miR-195-5p expression in rat cardiomyocytes is upregulated by high glucose stimulation [148]. Here, it was shown that silencing miR-195-5p rescues high-glucoseinduced hERG potassium ion channel deficiency by restoring serum and glucocorticoid-regulated kinase 1 (SGK1) expression [148].…”
Section: Dysregulated Mirnas In Gestational Diabetes Mellitusmentioning
confidence: 99%
“…High glucose alone can promote pathological cardiac development by accelerating hypertrophy, promoting ER stress, increasing ROS production, and ultimately leading to apoptosis (Ng et al, 2018;Zhang X. et al, 2018;Shi et al, 2019). When uncoupled from oxidative phosphorylation, glycolysis produces glycolytic intermediates that can accelerate flux through nonanapleurotic pathways, such as the pentose phosphate pathway (PPP), hexosamine biosynthetic pathway, or lactate shuttling (Gupte et al, 2006;Gibb et al, 2017).…”
Section: Glucotoxicitymentioning
confidence: 99%
“…For instance, elevation of miRNA-195 upregulates multiple genes associated with hypertrophic development. Exogenous administration of this oligonucleotide can promote hypertrophy and alter cardiac mitochondrial function, while the complementary oligonucleotide provides a protective effect (Shi et al, 2019;Wang et al, 2019). Lastly, increased use of glucose has been shown to induce cell growth (Kolwicz et al, 2013;Shao et al, 2018) and alter epigenetic regulation in the nucleus (Shao et al, 2018;Lombardi et al, 2019).…”
Section: Glucotoxicitymentioning
confidence: 99%